SUSTAINABILITY OF URBAN AREA DEVELOPMENT BASED ON THE AVAILABILITY OF GREEN OPEN SPACE IN MEDAN CITY - Gusti Elcitra Limbong; Feby Milanie (Bulletin of Engineering Science, Technology and Industry, 2024)
The sustainability of urban development in Medan City is greatly influenced by the availability of Green Open Space (RTH) that can support environmental quality and the quality of life of the community. Medan City, as a city with a high level of urbanization and increasing population density, faces challenges in providing sufficient green space. The mismatch between the allocation of RTH in the Regional Spatial Plan (RTRW) and the existing land use conditions, as well as the limited space for RTH development in densely populated areas, are the main factors in the decline in environmental quality. Limited RTH reduces the ability of urban ecosystems to manage air pollution, temperature, and rainwater absorption. In addition, limited RTH also has a negative impact on the physical and mental health of the community. Therefore, efforts to increase the availability of RTH need to be carried out with an approach that involves the development of vertical green spaces, small city parks, rehabilitation of abandoned spaces, and improvement of spatial planning policies. This study aims to analyze the importance of the role of RTH in the sustainability of urban area development and the solutions that can be applied to achieve it, in order to create a greener, healthier, and more sustainable city environment.